Metafore dello spazio - Bruna, Consarelli (Firenze University Press, 2004)
This book on Metafore dello spazio, which follows the first dealing with La politica e gli spazi politici, is part of a series designed to illustrate the results of an interdisciplinary study group, fostered by Lea Campos Boralevi, Vittore Collina and Bruna Consarelli, lecturers in the history of political theory, entitled Figure dello spazio, politica e società, and aimed at exploring the major political and social issues of the modern and contemporary age from the aspect of spaces and their production.